FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PETANI MENJUAL LAHAN PERKEBUNAN KOPI KE PERUSAHAAN TAMBANG BATUBARA - Kesumariani, Pipin; ., Suharno; Ekayani, Meti (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2018)
Coffee is one of the main commodities of Indonesian plantation crops. During 2012-2016 South Sumatera Province is the largest coffee producer with a contribution 28.80%. Beside as coffee producer, South Sumatera Province has a coal mining potential as much as 38,5% from the national total supply (22.240,4 million ton). The development of coal industry causes coffee land conversion. The purpose of the study is to analyze the factors that determine the farmer’s decision to sell their cropland to coal mining investor. The research was conducted in Lahat Regency, South Sumatera Province on February-March 2018. The sampling method used simple random sampling, with a total sample of 52 respondents. The research showed that land aggregates, total farmer’s income, number of families and age of coffee plant significantly influence farmer’s decision. Land conversion is a natural phenomenon that could not be prevented, but it could be controlled with restricting the license of coal mining, space arrangement (RTRW) and provide incentives to farmers as a form of support from the Government.